PERIKATAN BERSYARAT DAN BEBERAPA PERMASALAHANNYA - Budiono, Herlien (Faculty of Law, Parahyangan Catholic University, 2016)
Unpredictability is a factor which has always to be dealt with when making contracts and is related to some act (juridical) which may or may not happen. This unpredictability may be the result of an act/commission or ommission to be perfomed by an unknown person, known person or a third person. In respons to this unpredicability, to a contract can be added a conditionality in which failure to meet certain conditions will result in postponement or cancellation. Conditionality may also be employed in making one sided juridical acts, such as a will or a power of attorney. A contract in which one or both parties is required to obtain prior consent before the contract can be performed is a conditional contract. A conditional contract differs from a contract with a time-limit and contract with an obligation. In addition, there are impossible condition, inevitable condition, unlawful condition, indecent condition, potestatif condition, and incomprehensible condition. In regard to a will, attention must be given to the difference between fideï-commis and contract with an obligation. A contract with the conditionality of annulment also differs from an obligation to stand for a surety. The law regulation in articles 1266 and 1267 KUHPerdata acknowledges the conditionality related to annulment which is always assumed in reciprocal contract. Keywords:contract, agreement, conditional, annulment, postponement, unpredictable